PEMANFAATAN KONSENTRAT PROTEIN IKAN PATIN (Pangasius hypopthalmus) UNTUK PEMBUATAN BISKUIT DAN SNACK - . Dewita; . Syahrul; . Isnaini (Jurnal Pengolahan Hasil Perikanan Indonesia, 2011)
Patin  sh (Pangasius hypopthalmus) is one of fresh water  shes commonly cultured in Indonesia particularly in Riau Province. The purposes of these research were determined characteristic of organoleptic value and nutrition of sh concentrate protein (FPC), and also utilized the FPC in making biscuit and snack. The biscuits were made by adding wheat  ours, patin  sh protein concentrate, margarines, sugars and chicken egg. The snacks were composed from wheat  ours, patin  sh protein concentrate, seasonings and chicken egg. The preference test was conducted in this research involved organoleptic parameters, and chemical tests. The results showed that food snacks and biscuits made from Patin Fish Protein Concentrate were well accepted through organoleptics tests and nutrition contains. The nutrition contains for its biscuits were 4,05% of moisture content, 2.44% of ash, 19.47% of Protein, 21.91% of Fat and 52.13% of carbohydrate, while the nutrition contains for its snacks were 4.38% of moisture content, 2.39% of ash, 19.14% of protein, 30.77% of fat, and 46.32% of carbohydrate.Keywords : concentrate, protein, patin, snacks, biscuits